2015
DOI: 10.1097/01.aog.0000463686.74252.e3
|View full text |Cite
|
Sign up to set email alerts
|

Do Elastic Abdominal Binders Reduce Postoperative Pain and Blood Loss?

Abstract: modulators. DNA methytransferases (DNMT) appear to regulate gene activity during decidualization, but relative expression level by phase is not fully understood and has not been studied in abnormal uterine bleeding.METHODS: Immunohistochemistry was performed on tissue microarrays derived from 541 endometrial samples including secretory, proliferative, atrophic histopathologic diagnoses. Baseline demographic and clinical data were collected for all 541 study participants. The expression levels of DNMT1, DNMT3a,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…A few studies have examined the effects of abdominal binders on CS complications (21,23,27). Some have addressed how abdominal binders impact wound healing (20,22,24) and pain medication consumption (21, 30) post-surgery.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A few studies have examined the effects of abdominal binders on CS complications (21,23,27). Some have addressed how abdominal binders impact wound healing (20,22,24) and pain medication consumption (21, 30) post-surgery.…”
Section: Discussionmentioning
confidence: 99%
“…However, the intervention group consumed significantly less pain medication than the control group at other intervals. In a number of similar studies on the effects of abdominal binders postlaparotomy and major abdominal procedures (Ali et (21) and between the first and fifth day post-major abdominal and laparotomy, using the SF-MPQ (Cheifetz et al, 2010) (18). Christoffersen (2014) demonstrated the ineffectiveness of using an abdominal binder post-surgery in umbilical and epigastric hernia repair; movement limitations, fatigue, quality of life, seroma formation, and pain remained unimproved (33).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies has shown that use of an elastic abdominal binder reduces postoperative pain and distress. 7,13,14 Postoperative pain also influenced breastfeeding and infant care. 15 Our study showed the decrease of pain in abdominal binder; the benefit of elastic abdominal binders after cesarean section in rural area volume 22, issue 3, July -september 2023 *p-value was analyzed using non-parametric Mann-Whitney U test however, it was not different for SDS and BPI-SF in terms of pain's impact to daily life.…”
Section: Discussionmentioning
confidence: 99%